2014
DOI: 10.1515/polyeng-2014-0175
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids and poly(amino acids) as nucleating agents for poly(lactic acid)

Abstract: Abstract:In industry, rapid crystallization is often required. At present, the crystallization rate of poly(lactic acid) (PLA) is too low compared to industrial needs. In this paper, amino acids such as glycine and L-alanine and poly(amino acids) like polyglycine and poly-DL-alanine are considered as heterogeneous crystallization nucleating agents. The impact of adding these bio-based additives on the isothermal crystallization behavior of PLA was quantified and compared at different concentrations by using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…In order to promote the crystallization of PLLA without compromising its bio-advantages, several biobased NAs with biodegradability, biocompatibility and nontoxicity like myoinositol, 32 thermoplastic starch, 33 orotic acid, 34 nucleobases, 35 xylan esters, 36 cyclodextrin complex, 37 lignin, 38 nanocelluloses, 39,40 amino acids and poly(amino acids) 41 have been developed. Among of these biobased NAs, it appears that orotic acid (OA), a naturally occurring substance (e.g., in milk products), is most effective in light of the signicant enhancement on crystallization kinetics of PLLA with only 0.3 wt% dosage (crystallization peak temperature is 123.…”
Section: -9mentioning
confidence: 99%
“…In order to promote the crystallization of PLLA without compromising its bio-advantages, several biobased NAs with biodegradability, biocompatibility and nontoxicity like myoinositol, 32 thermoplastic starch, 33 orotic acid, 34 nucleobases, 35 xylan esters, 36 cyclodextrin complex, 37 lignin, 38 nanocelluloses, 39,40 amino acids and poly(amino acids) 41 have been developed. Among of these biobased NAs, it appears that orotic acid (OA), a naturally occurring substance (e.g., in milk products), is most effective in light of the signicant enhancement on crystallization kinetics of PLLA with only 0.3 wt% dosage (crystallization peak temperature is 123.…”
Section: -9mentioning
confidence: 99%
“…The authors found that LAK301 acted as a very efficient nucleating agent by increasing crystallinity percentage from 5.6% in pure PLA [5]. Amino acids and poly(amino acids) were used as nucleating agents for PLA by Carbone et al in 2015 [6]. They indicated that polyglycine possessed a significant nucleating ability.…”
Section: Introductionmentioning
confidence: 99%
“…Such a unique packing (supramolecular structure) gives polyglycine‐II attractive mechanical properties . Polyglycine is used for developing modified electrodes for electrochemical sensing of various chemicals, solid pH sensor and improving the properties of thermoplastics . In addition, polyglycine domains in natural proteins such as silk are shown to play important role in the mechanical properties of such proteins .…”
Section: Figurementioning
confidence: 99%